EFISIENSI BAITUL MAL WA TAMWIL (BMT) DI SURABAYA TAHUN 2012-2017 DENGAN DATA ENVELOPMENT ANALYSIS (DEA) - Valencia Kirana Rosadhillah; Fatin Fadhilah Hasib (Universitas Airlangga, 2022)
This study aims to find out whether Islamic microfinance, especially in Baitul Maal wat Tamwil in Surabaya has reached the level of efficiency in its operational activities from or not. This research uses a quantitative approach within Data Envelopment Analysis (DEA) technique. This study uses primary data which directly retrieves Islamic microfinance financial report data from Islamic microfinance. The results showed that the efficiency value of Variable Returns to Scale (VRS) processing was higher than the Constant Returns to Scale (CRS) processing result. From five BMT that become research objects of this study, just one institution that pass efficiency level and able to optimally use its resources (inputs) to produce certain outputs. On the assumption of CRS and VRS, most of Islamic Microfinance in Surabaya has not been efficient from 2012-2017 and Islamic microfinance in Surabaya is on the scale of diseconomies, that is Islamic Microfinance in Surabaya not yet optimally in empowering its resource (input) to produce output. So that Islamic microfinance in Surabaya must make improvements in managing inputs in order to improve efficiency value by doing selective funding to avoid default payment and the increase of uncollectible accounts expense. Each BMT has a different efficiency level that need to improved by treatment, including reduce operational expenses, reduce assets, and increase income. The implication of this study is an improvement strategies for each BMT to get their efficiency level betterment.